UPACARA RELIGI DAN PEMASARAN PARIWISATA DI PROVINSI BENGKULU - . Yuliati (Universitas Tribhuwana Tunggadewi, 2016)
Abstract: The goal of this research is to investigates the processes of commoditization of the ceremonial festival of Tabot for the benefit of tourism marketing in the Province of Bengkulu. The study is a qualitatively descriptive, the data were obtained from literatures and also collected from interviews, documentation and other library researches. The data collection technique used was purposive sampling. The technique of analyzing the data used was the one that applied the model of interactive analysis. And the validity of the data was obtained through the technique of Triangulation of Patton. Tabot Festival is a program created by the State Tourism Office in cooperation with the Family of Tabot Harmony to improve the potential tourism asset to be a tourism commodity. The festival is held in various arts and cultural events like the competition of Telong-Telong, Ikan-Ikan, music of Dol, Tabot dances, Sarafal Anam, traditional pop songs, and national arts. It is an important festival for Bengkulunese that has met the requirements of originality, scarcity, and wholesomeness as a valuable asset for being better and professionally packaged in order to improve the development of tourism in Bengkulu. The communication media used for popularizing the festival and for making it easily informed are the media of marketing communication i.e. printed and electronic media such as brochures or leaflets. Keywords: religious ceremony, tourism marketing, commoditization Abstrak: Tujuan penelitian ini adalah untuk mengetahui proses-proses komodifikasi terhadap upacara Tabot untuk kepentingan pemasaran pariwisata Propinsi Bengkulu. Jenis penelitian yang digunakan adalah deskriptif kualitatif, sumber data diperoleh dari kepustakaan. Sedangkan pengumpulan datanya dari wawancara, dokumentasi dan penelitian pustaka. Teknik pengumpulan data yang digunakan adalah purposive sampling. Teknik analisis data dalam penelitian ini menggunakan model analisis interaktif. Validitas data yang digunakan adalah teknik triangulasi patton. Festival Tabot merupakan program yang dibuat Dinas Pariwisata yang bekerjasama dengan Kerukunan Keluarga Tabot untuk pengembangan potensi pariwisata sebagai komoditas pariwisata. Tabot sebagai kebutuhan masyarakat Bengkulu telah memenuhi persyaratan, keaslian (Originality), kelangkaan (Scarsity), keutuhan (Wholesomeness) sebagai asset yang sangat berharga untuk dikemas lebih baik secara professional dalam perkembangan kepariwisataan di Bengkulu. Media komunikasi yang digunakan agar masyarakat luas dengan mudah mengakses informasi mengenai Tabot adalah dengan media komunikasi pemasaran yang dilakukan melalui media cetak dan media elektronik serta membuat selebaran atau leafet. Kata kunci : Upacara religi, pemasaran pariwisata, komodifikasi